2014
DOI: 10.1038/nature13263
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal oxygenases are structurally conserved from prokaryotes to humans

Abstract: 2-Oxoglutarate (2OG)-dependent oxygenases play important roles in the regulation of gene expression via demethylation of N-methylated chromatin components1,2, hydroxylation of transcription factors3, and of splicing factor proteins4. Recently, 2OG-oxygenases that catalyze hydroxylation of tRNA5-7 and ribosomal proteins8, have been shown to play roles in translation relating to cellular growth, TH17-cell differentiation and translational accuracy9-12. The finding that the ribosomal oxygenases (ROX) occur in org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 59 publications
7
134
0
1
Order By: Relevance
“…18 Structurally, MINA protein contains a conserved jumonji C (JmjC) domain that belongs to the histone demethylases family. 19 It has been reported that MINA is involved in reducing the trimethylation of histone H3K9 (H3K9me3). 10,20 Histone demethylases are known to regulate gene transcription by altering the methylate status on histones, 21 but their roles in cancers and the underlying molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…18 Structurally, MINA protein contains a conserved jumonji C (JmjC) domain that belongs to the histone demethylases family. 19 It has been reported that MINA is involved in reducing the trimethylation of histone H3K9 (H3K9me3). 10,20 Histone demethylases are known to regulate gene transcription by altering the methylate status on histones, 21 but their roles in cancers and the underlying molecular mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our structural studies exploited catalytically inactive Ni 2+ -substituted enzymes to minimize oxidative damage to the enzyme. This strategy has been used with great success in investigations of Fe(II)/AKG-dependent oxygenases, for example, in the histone demethylases (23)(24)(25). Other work has demonstrated that metal substitution does not alter the coordination within the error of crystallographic resolution (26).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Chowdhury et al recently reported on structural differences within the Jmj family, for example between the ROX enzyme NO66 and KDM4A [36]. More specifically, KDM family members only remove methyl groups from the terminal nitrogen of lysine side-chains, therefore their target residues do not penetrate as far into the active site.…”
Section: Comparison With Other 2-og-dependent Oxygenasesmentioning
confidence: 96%
“…ROXs and certain hydroxylases, such as FIH, form homodimers through interactions between alpha helical dimerisation domains and this oligomerisation is important for protein activity [36]. [39].…”
Section: Dimerisationmentioning
confidence: 99%